Cross-species amplification of Aquilaria microsatellites across thirteen agarwood-producing species and genetic structure of Aquilaria Beccariana tiegh. in Malaysia - Pern, Yu Cong (2019)
Tree species in the Aquilarieae tribe produce agarwood, a natural product, highly valued for its compound-rich fragrance. However, these resources in the wild are under threat from agarwood demand in the international market. DNA profiling approaches have been utilized for tree conservation purposes.Unfortunately, this effort is hampered by the lack of suitable molecular markers and the challenges to obtain resources due to the endangered status of the species. In several Aquilaria species, microsatellite markers have been developed but cross-species amplification and evaluation has yet to be examined. In this study, 30 microsatellite markers, developed for Aquilaria malaccensis, Aquilaria crassna and Aquilaria sinensis, were selected and crossamplified in ten Aquilaria and three Gyrinops species, all from the Aquilarieae tribe. Cross-species amplification of 18 perfect dinucleotide microsatellite markers (Ama040, Ama067, Ama101, Ama114, Ama131, Ama144, Ama263, Ama264, Ama331, Ama338, 16pa17, 71pa17, BMX1, BMX3, BMX6, BMX7, BMX8, and AQEGMS-53) on the 13 species revealed a high probability of amplification success (86%) and identified a total of 300 alleles with PIC ranged from 0.5770 to 0.9244. The mean gene diversity (HE) and heterozygosity (Ho) were 0.8598 and 0.3641, respectively. Species-specific alleles and genotype were tabulated as a substitute for DNA fingerprinting profile. The high crossspecies amplification rate of the selected microsatellite markers displays high genetic variability among the species. Among the Aquilaria species native to Malaysia, Aquilaria beccariana is found distributed in the Malay Peninsula and Borneo Island. To study their phylogeographical relationship and genetic relatedness, fresh leaf samples of 47 individuals from five different wild populations (Mersing in Johor; Long Banga, Ba’lai, and Lawas in Sarawak; Sungai Kangkawat in Sabah, and Kalimantan, Indonesia) were collected. Using PCR, seven non-coding chloroplast DNA (cpDNA) regions and a nuclear ribosomal DNA (nrDNA) region were amplified and sequenced. Phylogenetic, median-joining, and Principal Coordinate Analysis (PCoA) analyses assembled the five populations into two major clusters, Malay Peninsula and Borneo. Trees in Borneo were further clustered into Central, Northern, and Southern populations. DNA barcode data generated from this study serve as important reference to support species identification. In addition, a population distribution map was generated for several Aquilaria species based on published herbarium data, previous reports and this study. In conclusion, this work provides useful information about marker cross ability and genetic relationships of several agarwood-producing species, both of which may help in the management and conservation of agarwood resources.